Carbon dioxide direct air capture for effective climate change mitigation based on renewable electricity: a new type of energy system sector coupling - Breyer, Christian; Fasihi, Mahdi; Aghahosseini, Arman (Mitigation and adaptation strategies for global change, 2020)
Pathways for achieving the 1.5–2 °C global temperature moderation target imply a massive scaling of carbon dioxide (CO 2 ) removal technologies, in particular in the 2040s and onwards. CO 2 direct air capture (DAC) is among the most promising negative emission technologies (NETs). The energy demands for low-temperature solid-sorbent DAC are mainly heat at around 100 °C and electricity, which lead to sustainably operated DAC systems based on low-cost renewable electricity and heat pumps for the heat supply. This analysis is carried out for the case of the Maghreb region, which enjoys abundantly available low-cost renewable energy resources. The energy transition results for the Maghreb region lead to a solar photovoltaic (PV)-dominated energy supply with some wind energy contribution. DAC systems will need the same energy supply structure. The research investigates the levelised cost of CO 2 DAC (LCOD) in high spatial resolution and is based on full hourly modelling for the Maghreb region. The key results are LCOD of about 55 €/t CO2 in 2050 with a further cost reduction potential of up to 50%. The area demand is considered and concluded to be negligible. Major conclusions for CO 2 removal as a new energy sector are drawn. Key options for a global climate change mitigation strategy are first an energy transition towards renewable energy and second NETs for achieving the targets of the Paris Agreement.